2022
DOI: 10.1007/s00701-022-05277-9
|View full text |Cite
|
Sign up to set email alerts
|

Early thrombocytopenia is associated with an increased risk of mortality in patients with traumatic brain injury treated in the intensive care unit: a Finnish Intensive Care Consortium study

Abstract: Background Coagulopathy after traumatic brain injury (TBI) is associated with poor prognosis. Purpose To assess the prevalence and association with outcomes of early thrombocytopenia in patients with TBI treated in the intensive care unit (ICU). Methods This is a retrospective multicenter study of adult TBI patients admitted to ICUs during 2003–2019. Thrombocytopenia was defined as a platelet count < 100 × 109/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…This elevation of MA is similar in the numbers reports in previous works of trauma patients that has been linked to increased risk of thrombotic complications (MA, 71.9 mm in patients with thromboses vs. 68.5 mm in patients without thromboses, compared with 74.4 mm post-dura violation vs. 63.5 mm pre-dura violation in our patients), 28 suggesting these changes observed in MA in our data have clinical significance. The increased platelet-mediated clot strength in our patients may be an important player in mitigating the locally hypocoagulopathic environment of hemorrhagic cerebrum, as evidenced by prior reports of higher maximum clot firmness (another viscoelastic metric of clot strength) in TBI survivors versus nonsurvivors 29 and poorer outcomes in TBI patients with thrombocytopenia 30 …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This elevation of MA is similar in the numbers reports in previous works of trauma patients that has been linked to increased risk of thrombotic complications (MA, 71.9 mm in patients with thromboses vs. 68.5 mm in patients without thromboses, compared with 74.4 mm post-dura violation vs. 63.5 mm pre-dura violation in our patients), 28 suggesting these changes observed in MA in our data have clinical significance. The increased platelet-mediated clot strength in our patients may be an important player in mitigating the locally hypocoagulopathic environment of hemorrhagic cerebrum, as evidenced by prior reports of higher maximum clot firmness (another viscoelastic metric of clot strength) in TBI survivors versus nonsurvivors 29 and poorer outcomes in TBI patients with thrombocytopenia 30 …”
Section: Discussionsupporting
confidence: 52%
“…The increased platelet-mediated clot strength in our patients may be an important player in mitigating the locally hypocoagulopathic environment of hemorrhagic cerebrum, as evidenced by prior reports of higher maximum clot firmness (another viscoelastic metric of clot strength) in TBI survivors versus nonsurvivors 29 and poorer outcomes in TBI patients with thrombocytopenia. 30 Beyond the cellular contributions to the pathologic hypercoagulability of TBI, our data highlight an important transition to fibrinolytic shutdown and tPA resistance. There has been controversy in the literature as to whether TBI drives a hyperfibrinolytic or antifibrinolytic phenotype.…”
Section: Discussionmentioning
confidence: 77%
“…Tsuneoka et al 3 and Engström et al 13 found that TBI caused a decrease in platelets, and thrombocytopenia could predict the short‐term prognosis of these patients. A recent study 24 also suggested that 12% of TBI patients treated in the ICU developed early thrombocytopenia and that thrombocytopenia was associated with an increased risk of mortality in these patients. These studies are consistent with our findings regarding the association between thrombocytopenia and short‐term mortality in patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of platelet levels, thrombopenia has been reported to increase mortality in TBI ( 31 ), especially in moderate–severe TBI. Thrombopenia facilitates bleeding and the progression of cerebral edema, which leads to an increase in intracranial pressure and a decrease in cerebral perfusion pressure ( 32 ).…”
Section: Discussionmentioning
confidence: 99%